A Novel model for simulating the integration process of hydraulic fracturing, shut-in period, and well production - Li, Yongming; Luo, Ang; Chen, Xi; Cheng, Leiming; Chang, Cheng; Xie, Weiyang (Frontiers in Energy Research, 2022)
Distributions of pore pressure and water saturation in matrix around fractures after hydraulic fracturing and shut-in period will impact the shale gas well production significantly. However, the influences of hydraulic fracturing and shut-in period on pore pressure and water saturation are not considered in the classical reservoir simulations. In this work, the embedded discrete fracture model (EDFM), which is convenient to be coupled with an existing reservoir simulator with high computational efficiency, was employed to simulate the hydraulic fracture propagation coupled with matrix flow. Then, we developed a model for simulating the integration process of hydraulic fracturing, shut-in period, and well production based on the dual media theory. Distributions of pore pressure and water saturation varying in different periods and the production decline of shale gas well were obtained through the integrated simulation model. The calculation result was validated by the field bottom hole pressure data of a shale gas well in Sichuan Province, China. Simulation results show that the variation of bottom hole pressure is not smooth during the fracture propagation process because the initiations of different fractures are not simultaneous. The fracturing fluid flow-back rate of shale gas well is much lower than that of conventional reservoirs. There is still a large amount of fracturing fluid retained in micro-fracture systems and matrix of shale after production. It is also found that the permeability of the micro-fracture system determines the drop rate of bottom hole pressure and the size of stimulated reservoir volume (SRV) determines the decrease amplitude of bottom hole pressure.